2015
DOI: 10.1002/mdc3.12286
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Cardiovascular Events and Nonergot Dopamine Agonists in Parkinson's Disease

Abstract: Background Knowledge of possible cardiovascular risks from Parkinson's disease (PD) medications is critical to informing safe and effective treatment decisions. The objective of our study was to determine whether PD patients treated with nonergot dopamine agonists (DAs) are at increased risk of adverse cardiovascular or cerebrovascular outcomes, relative to PD patients receiving other treatments. Methods Matched case‐control studies were conducted within a cohort of 14,122 inpatients receiving treatment for PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…An association between the use of ergot DAs (pergolide initially) and valvular heart toxicity was reported in the early 2000s [113]. Whilst non-ergot DAs might have seemed an obvious alternative, reports then emerged of side effects associated with their use [114118]. Although in several studies the non-ergot prescription rate increased, particularly after pergolide withdrawal [46, 47, 51, 53, 54, 62], the prescription rates decreased in the USA in 2011 [51].…”
Section: Discussionmentioning
confidence: 99%
“…An association between the use of ergot DAs (pergolide initially) and valvular heart toxicity was reported in the early 2000s [113]. Whilst non-ergot DAs might have seemed an obvious alternative, reports then emerged of side effects associated with their use [114118]. Although in several studies the non-ergot prescription rate increased, particularly after pergolide withdrawal [46, 47, 51, 53, 54, 62], the prescription rates decreased in the USA in 2011 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine agonist can alter blood pressure, mainly by promoting hypotension. Observational studies and meta-analysis RCTs raised no concerns regarding an association with increased risk of IS 77,78 (E).…”
Section: (C)mentioning
confidence: 99%
“… 2–4 Although a recent systematic review found no association between IHD and PD, the review concluded that other cardiovascular events, such as stroke, have such an association. 1 However, this should not exclude IHD and other cardiovascular risks in PD patients, given that other factors can impact this association, such as the cardiac side effects of some PD medications (eg, dopamine agonists), 5 , 6 and the use of antidepressants and antipsychotics in PD patients. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%